Charles Kennedy 1923-1997: An Appreciation - A.P. Thirlwall (University of Kent, Department of Economics, 1998)
Charles Kennedy, Honorary Professor of Economic Theory at the University of Kent at Canterbury, died from a pulmonary haemorrhage at his home on 4th November 1997, aged 74. This paper is an appreciation of his life and work.
Keywords: 330; Großbritannien